2010
DOI: 10.1007/s11552-010-9298-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute Carpal Tunnel Syndrome Secondary to Iatrogenic Hemorrhage. A Case Report

Abstract: Carpal tunnel syndrome is a common compression neuropathy of the median nerve. Acute carpal tunnel syndrome (aCTS) is rare, associated with a variety of conditions. In this case report we present a patient who developed aCTS and volar forearm compartment syndrome after a radial artery line placement, while receiving intravenous heparin. The patient underwent immediate forearm fasciotomy and surgical release for restoration of nerve function, which resulted in improved hand function and mild residual median ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…They consisted of an iatrogenic carpal tunnel syndrome and carpal tunnel syndrome with sequelae of complex regional pain syndrome. In both reports, neuropathies were due to hematomas, whereas our reported iatrogenic carpal tunnel syndrome was not related to hematomas [ 3 , 4 ]. Our patient had none of the risk factors for carpal tunnel syndrome such as diabetes, rheumatism, or amyloidosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They consisted of an iatrogenic carpal tunnel syndrome and carpal tunnel syndrome with sequelae of complex regional pain syndrome. In both reports, neuropathies were due to hematomas, whereas our reported iatrogenic carpal tunnel syndrome was not related to hematomas [ 3 , 4 ]. Our patient had none of the risk factors for carpal tunnel syndrome such as diabetes, rheumatism, or amyloidosis.…”
Section: Discussionmentioning
confidence: 97%
“…The complications reported include occlusion of the radial artery, hematoma, and nerve injury [ 2 ]. However, complications related to radial artery catheterization are not limited to those owing to direct injury during the procedure [ 3 , 4 ]. We report a case of iatrogenic carpal tunnel syndrome induced by wrist extension for indwelling radial artery catheter placement.…”
Section: Introductionmentioning
confidence: 99%
“…CTS symptoms progress in months to years, but in acute CTS, symptoms progress very quickly in hours to days. This condition usually occurs after traumatic events [4]. Rarely, carpal tunnel syndrome may occur with atraumatic etiology such as infection, inflammation, and iatrogenic events that increase carpal tunnel pressure [4, 5].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our case is the first patient with rheumatoid arthritis on methotrexate and warfarin who developed spontaneous median intraneural hemorrhage causing ACTS and had successful surgical open decompression. We found a few case reports [2][3][4][5][6][7][8][9] dating back to 1986, describing ACTS in patients on anticoagulation medication. The collection of case reports showed that five out of the seven patients were on longterm warfarin therapy, while one patient was on aspirin, one was on dabigatran and another on apixaban.…”
Section: Orthopedics and Rheumatology Open Access Journal (Oroaj) Discussionmentioning
confidence: 99%